The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0100-55022007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Homeopatia: desinformação e preconceito no ensino médico

Abstract: Embora a homeopatia seja uma especialidade médica reconhecida pelo Conselho Federal de Medicina desde 1980, com pressupostos científicos estabelecidos, aplicação clínica diversa, projetos nas áreas de pesquisa básica e clínica, oferecida nos serviços públicos de saúde e com iniciativas de ensino na graduação médica, a desinformação sobre esta peculiar racionalidade se encontra arraigada na cultura médica. Este estudo objetivou mensurar a desinformação quanto aos pressupostos homeopáticos existente entre estuda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
0
7
0
8
Order By: Relevance
“…Promoting the introduction of the theme in the curricula of courses in the area of health would be a measure to be considered. 18,20 In most cases, such courses do not provide knowledge about other types of medicine and therapies, including These data emphasize the current paradox, where a high level of social medicalization, belief in science and biomedicine and consistent growth in the search for other types of care coexist. 11,21 Results of the present study do not provide in-depth analyses or explanations about the position of most professionals, although they suggest that there is sensitization to the social movement to revalue CIT.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting the introduction of the theme in the curricula of courses in the area of health would be a measure to be considered. 18,20 In most cases, such courses do not provide knowledge about other types of medicine and therapies, including These data emphasize the current paradox, where a high level of social medicalization, belief in science and biomedicine and consistent growth in the search for other types of care coexist. 11,21 Results of the present study do not provide in-depth analyses or explanations about the position of most professionals, although they suggest that there is sensitization to the social movement to revalue CIT.…”
Section: Discussionmentioning
confidence: 99%
“…Homeopathic medicine was introduced to Brazil in the XIX century and is currently ranked the 16th medical specialty with the largest contingent of professionals among 61 specialties analyzed in the survey conducted in 1996 7,8,23 . Nevertheless, only 17 schools of medicine among 115 analyzed in Brazil have been teaching homeopathic principles, and among these not all respect the minimum curriculum of 45 minutes per lesson as suggested by the Brazilian Homeopathic Medical Association 24 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Teixeira et al 7 , over 85% of the medical students at the University of São Paulo considered that homeopathy and acupuncture should be included in curricula, as options (72%) or compulsorily (19%); while 56% showed a great interest in learning about them. In another study conducted during a medical students' conference, Teixeira 8 found that 43% of students did not recognize homeopathy as a "medical specialty", they were all unaware that it was "available through public health services" 8 9 , only 40% (99) of 247 medical students, from the University of Campinas, correctly answered the questions about homeopathy principles and 25% of them were completely incorrect in their answers.…”
Section: Introductionmentioning
confidence: 99%
“…Analogamente, instituições acadêmicas passaram a desenvolver atividades de ensino e treinamento que valorizam as dinâmicas espirituais e religiosas na saúde integral dos pacientes, incorporando conceitos da metaantropologia ou antropologia espiritual à formação dos profissionais da saúde, ampliando a compreensão da natureza biopsicossocioespiritual humana e seu processo de adoecimento [80][81][82][83][84][85] Engana-se quem despreza a incorporação desses contributos filosóficos, vitalistas e espirituais à prática médica moderna, pois, além de incrementar a resolutividade das doenças e tornar a relação médico-paciente mais humanizada, amplia o entendimento do processo integralizante do adoecimento humano (corpo-menteespírito), aspectos bastante valorizados em pesquisas que levantaram os motivos da procura pela população e pela classe médica por terapêuticas não convencionais [88][89][90][91][92][93] .…”
Section: Conclusõesunclassified